Analysis of bioelectric potential of cabbage waste (Brassica oleraceae var. capitata) using microbial fuel cells - Vita Meylani; Elsa Nurfauziah; Diana Hernawati (Journal of Agriculture and Applied Biology, 2022)
Vegetable waste, one of which is cabbage waste, has long been recognized as a cause of a significant environmental problems in traditional markets and must be addressed. However, cabbage waste can be used as an alternative energy source through the Microbial Fuel Cell process. The purpose of this study was to determine the potential of cabbage waste as a producer of bioelectricity and the storage time of cabbage waste that produces the largest bioelectricity using Microbial Fuel Cells. This research was conducted in February 2022 at Laboratory of Microbiology and Botany, Universitas Siliwangi. The study employed a completely randomized design (CRD), with treatment consisting of a control group (without storage), five storage treatments, namely: treatment 1 (2 days storage), treatment 2 (4 days storage), treatment 3 (6 days storage), treatment 4 (eight days storage), and treatment 5 (10 days storage). All treatments were repeated 4 times. A digital multimeter is used to determine the resulting electric current. The results indicated that the highest average total electric current generated was 0.022 mA from the 4 days storage treatment. The lowest average total electric current generated was 0.010 mA from the 10th days storage. These data indicate that the treatment of storage time of up to 4 days can increase the amount of electric current generated, then it decreases with increasing length of storage. It is influenced by several variables, including the growth phase of the bacterium, the availability of organic molecules, and the population of bacterium.